2014
DOI: 10.1111/psyp.12251
|View full text |Cite
|
Sign up to set email alerts
|

The persistence of socially instructed threat: Two threat‐of‐shock studies

Abstract: Learning to anticipate threat is crucial in guiding protective behavior. In classical conditioning, single trial learning can result in long-lasting fear associations. To examine whether threat learned through social communication is equally stable, an instructed fear paradigm was used with two repeated sessions on 1 day (Study 1; N = 43) and with separate sessions on 3 consecutive days (Study 2; N = 30). Startle EMG, skin conductance level (SCL), and self-report data were recorded during alternating periods o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 66 publications
5
59
0
Order By: Relevance
“…In the IT group instead, threat persist over time and even might increase in the course of the experiment. In support for this hypothesis, Bublatzky et al (2014) found that a verbal threat instruction persists over multiple experimental sessions and even longer periods (up to 3 days) without any actual experience of the UCS. On the neural level, the interaction of threat and pain revealed a stronger activation of the amygdala (and to a lesser degree of neighboring hippocampal areas) for the CT group (see Table 3, Figures 4 and 5).…”
Section: Discussionmentioning
confidence: 74%
“…In the IT group instead, threat persist over time and even might increase in the course of the experiment. In support for this hypothesis, Bublatzky et al (2014) found that a verbal threat instruction persists over multiple experimental sessions and even longer periods (up to 3 days) without any actual experience of the UCS. On the neural level, the interaction of threat and pain revealed a stronger activation of the amygdala (and to a lesser degree of neighboring hippocampal areas) for the CT group (see Table 3, Figures 4 and 5).…”
Section: Discussionmentioning
confidence: 74%
“…Specifically, research on influences of emotional sounds on (subsequent) visual processing is pending. To account for physical differences of emotional picture and sounds, investigations with well controlled and (physically) comparable stimuli (e.g., with instructed fear or conditioning procedures) are urgently needed (see, e.g., Bröckelmann et al, 2011 ; Bublatzky et al, 2014a ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, though, threat cues elicit equivalent electrodermal reactions whether fear is instantiated through instructions or actual conditioning (Bridger & Mandel, 1964;Raes, De Houwer, De Schryver, Brass, & Kalisch, 2014), and instructions are also quite effective in quickly reversing explictly conditioned electrodermal responses (Grings et al, 1973;McNally, 1981;Wilson, 1968). Moreover, startle reflex potentiation remains elevated for up to 3 days to cues signaling threat of shock, even though threat cues were not followed by an actual shock reinforcer (Bublatzky, Gerdes, & Alpers, 2014). Finally, vividly imagining an aversive reinforcer during conditioning, without actually reexperiencing it, prolongs conditioned skin conductance responses (Jones & Davey, 1990).…”
Section: Discussionmentioning
confidence: 99%